Calidad de la atención y su influencia en la satisfacción de los usuarios del Servicio Integrado de Seguridad ECU911 Babahoyo, 2021 - Ortiz Campi, Oscar Patricio (2023)
The Ecuadorian public administration is considered very deficient, which makes it impossible to implement resources effectively; Its management system is so cumbersome that it does not allow the origin of its failure to be identified so that the nation's rulers can take effective measures for improvement. The requirements of the population increase every time, as does the magnitude of a state's resources, therefore, will depend on the good administration of the latter for the development of a nation, according to León (2018). According to Tonato (2017), in Ecuador, citizens in general have a poor perception of public services because the information or instructions provided to external users are often incorrect, as well as the quality of care, The inefficiency in the processes and the possibilities of finding solutions to their problems effectively generate distrust. The emergency service in the Ecuadorian territory called “ECU 911 Integrated Security Service” has as its fundamental function to provide an immediate and effective response service, coordinating in an articulated manner the attention of the organizations in cases of accidents, disasters, and emergencies, mobilizing resources available through a unique telematic means commonly known as 9-1-1, also made up of surveillance cameras, emergency and telephone buttons; The integrated institutions are: National Transit Agency and Traffic Commission of Ecuador, Municipality, Armed Forces, National Police of Ecuador, Ministry of Public Health, Red Cross, IESS, Fire Departments, Risk Management Secretariat (Acosta, 2022).